2017
DOI: 10.1155/2017/4651238
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Modulates CRIPTO-1/HNF4α+Cells to Guide Cardiac Differentiation from Human Embryonic Stem Cells

Abstract: The use of human pluripotent stem cells in basic and translational cardiac research requires efficient differentiation protocols towards cardiomyocytes. In vitro differentiation yields heterogeneous populations of ventricular-, atrial-, and nodal-like cells hindering their potential applications in regenerative therapies. We described the effect of the growth factor Activin A during early human embryonic stem cell fate determination in cardiac differentiation. Addition of high levels of Activin A during embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In agreement, whenever Activin-A was present, the number of spheres was reduced, exception made to the situation where only this cytokine was present. Corroborating this hypothesis are several reports in the literature indicating Activin-A as a differentiation inducer 32 34 .
Figure 5 IL-6 and Activin-A are the actual drivers of dedifferentiation.
…”
Section: Resultsmentioning
confidence: 63%
“…In agreement, whenever Activin-A was present, the number of spheres was reduced, exception made to the situation where only this cytokine was present. Corroborating this hypothesis are several reports in the literature indicating Activin-A as a differentiation inducer 32 34 .
Figure 5 IL-6 and Activin-A are the actual drivers of dedifferentiation.
…”
Section: Resultsmentioning
confidence: 63%
“…Among the top five hub genes identified in the protein-protein interaction network, only HNF4A (log 2 FC = 1.89, p < 2.92e −5 ), UBD (log 2 FC = 2.69, p < 7.37e −5 ) and EGR1 (log 2 FC = 1.47, p < 5.31e −12 ) were significantly and differentially upregulated in DMD-COs. Despite HNF4A could be linked to cardiac differentiation and heart development ( Duelen et al, 2017 ), we could not find in literature the association of these three hub genes with the development of cardiomyopathy, adipogenesis and fibrosis. We turned into looking at the identified miRNA regulators.…”
Section: Discussionmentioning
confidence: 67%
“…Among the top five hub genes identified in the protein-protein interaction network, only HNF4A (log 2 FC = 1.89, p<2.92e −5 ), UBD (log 2 FC = 2.69, p<7.37e −5 ) and EGR1 (log 2 FC = 1.47, p<5.31e −12 ) were significantly and differentially upregulated in DMD-CO. Despite HNF4A could be linked to cardiac differentiation and heart development (Duelen et al, 2017), we could not found in literature the association of these three hub genes with the development of cardiomyopathy, adipogenesis and fibrosis. We turned into looking at the identified miRNA regulators.…”
Section: Discussionmentioning
confidence: 74%